IMPROVING STUDENTS’ VOCABULARY USING FLASHCARD - Leonardus, Leonardus; Sada, Clarry; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe students were lacking of vocabulary. One of the factors was teaching media. In order to enrich the students’ vocabulary, the writer used flashcards as teaching media. The purpose of this research is to improve the students’ vocabulary using flashcards to The Eighth Grade Students Class C of SMPN 10 Pontianak. Based on the writer’s experiences during teaching, the students were lack of vocabulary. Therefore, this research is expected to find a solution to the students’ problem in mastering vocabulary. The method used in this research is a Classroom Action Research which consists of Planning, Acting, Observing, and Reflecting. This method was done in two cycles in order to get better result of the research. The subject of the study is Eighth Grade Students Class C of SMPN 10 Pontianak. The number if research participant is 38 students. The technique used for collecting data is by observation. The findings of this research were that the students’ progress during teaching and learning activity in classroom that the students did the discussion group and presented the result of the group discussion in front of the class. The students did the the assessment in the form of multiple choices after the discussion. Key Words: Vocabulary, Flashcard